Analysis Of Weakness In Enforcement Of Law Number 6 Of 2011 Concerning Immigration From Routine Activity Theory - Faridh Al Wajidi; Gina Isadora Patrecia Silalahi; Karina Karina (LEGAL BRIEF, 2022)
Law Number 6 of 2011 concerning Immigration regulates immigration law enforcement, both immigration administratif acts and immigration crimes. The implementation of immigration law enforcement is carried out by immigration officials who carry out their duties based on the applicable laws and regulations. However, the implementation of the implementation of Law Number 6 of 2011 cannot be said to be effective and in accordance with the reality. Today, the gap between das sollen and das sein in the application and enforcement of Law Number 6 of 2011, is so obvious that it is considered a routine activity. So, the formulation of the problem that will be examined in this paper is related to why there can be an application of the theory of routine activities in Law number 6 of 2011 and what is the effect of the theory of routine activities in immigration law enforcement in Law number 6 of 2011. This writing uses a qualitative research method with a qualitative approach. qualitative descriptive and data collection techniques carried out in a combined manner, namely inductive/qualitative. From the results of the study, it is known that the theory of routine activities in law enforcement as stipulated in Law No. 6 of 2011 resulted in many foreigners not complying with immigration rules properly due to the lack of strict enforcement of the applicable law.